Ciclos de aprendizagem e reprovação escolar: reflexões sobre representações sociais de professores (Práxis Educativa, 2009)
This paper presents aspects of the organization of the school in cycles and its relation with the retention practices based on the Theory of Social Representation (TRS) as well as studies on the schooling in cycles in Brazil. The research involved the analysis of interviews with 11 teachers of the state school system. The data analysis involved: content analysis, lexical analysis of content (software ALCESTE), and spontaneous classification of words. The findings pointed out that the repetition as central element of the teaching-learning relationships. Thus, the social representations of the teacher indicate that cultural factors overlap structural factors and it is essential aspects to understand the implementation of the schooling in cycles policy. Keywords: Schooling in cycles. Retention practices. Social representations.